Self-assembly of single-walled carbon nanotubes arrays with different line width. (10th September 2019) - Zhang, Jianwei; Wang, Xuewen; Mei, Huanhuan; Cheng, Yang; Xu, Muxun
Abstract: Single-walled carbon nanotubes (SWNTs) are one of the most promising nanoelectronic materials, However, there are still some application challenges, including purification, regular arrangement, interconnection, and so on. There is evidence that the array assembly can improve the performance of SWNTs. In this work, we develop a line-width controllable large-scale assembly of SWNTs based on aqueous solution, using electron beam (E-beam) lithography to construct self-assembled templates. The results show that SWNTs arrays of different line-width are obtained, which is possible to design the structure of SWNTs assembly to meet different functions.